Short-term antibiotic therapy for the most common bacterial respiratory infections in infants and children - Nicola Principi; Giovanni Autore; Alberto Argentiero; Susanna Esposito (Frontiers Media S.A., 2023)
Overuse and misuse of antibiotics have strongly accelerated the progressive increase in bacterial antimicrobial resistance (AMR). The evidence that antimicrobial selective pressure was greater the longer the antibiotic therapy was continued has led some experts to reconsider duration of antibiotic therapy testing the use of short-term drug administration. If as effective as long-term therapy, short-term therapy could have been an easy measure to limit AMR emergence. In the present narrative review, whether present knowledge on short-term therapy of acute streptococcal pharyngitis (ASF), acute otitis media (AOM) and mild to moderate community-acquired pneumonia (CAP) allows systematic use of short-term therapy in infants and children with these diseases is discussed. Literature analysis showed that reducing the duration of antibiotic therapy for some of the most common pediatric respiratory infections could be a valid measure to contain the antibiotic abuse and the consequent impact on the emergence of AMR. Several data seem to indicate that this type of intervention is possible, as short-term therapy has been found as effective as the traditionally recommended long-term therapy in some cases of ASF, AOM and mild to moderate CAP. However, further studies are needed to better characterize infants and children who can have benefit with short-term antibiotic therapy in common bacterial respiratory infections.